Strategic planning in agribusiness - Bittner, Beáta; Marczin, Tamás; Kovács, Tünde Zita (Acta Agraria Debreceniensis, 2023)
Agricultural businesses operate in a complex and dynamic environment, with many challenges and opportunities. It is therefore essential for these businesses to have a strategic plan. It is a critical process that helps businesses navigate in a complex and uncertain environment and achieve long-term goals and objectives. In this article, we have conducted a bibliometric analysis of academic journals to investigate the extent to which strategic planning is a researched topic in agribusiness enterprises. We found that there is no concentrated research, with only three keywords appearing in the literature with at least five repetitions. Even of the two repetitions, only 22 were found. The clustering of keywords helps to identify research directions. The results of a survey of 134 enterprises were then presented. The majority of enterprises do not have a long-term plan or even a written vision. We found that SWOT analysis is still the most common planning method among the companies surveyed. It was also found that there is no difference between industries in this respect. Significant differences were only found in relation to company size, with all large companies having a strategic plan and the vast majority of SMEs not. Only 17 out of 132 firms have a plan longer than three years, and 32 do not have any plan at all. Strategic planning can help to address many of the challenges in the agribusiness area, and it is therefore proposed to improve the proportion of firms planning through knowledge transfer.